The role of digitalization in the business turnover of women owned textile MSMEs in traditional markets: Evidence from Klewer market, Surakarta - Guritno, Danur Condro; Widya, Anisya Nur; Juwita, Aulia Hapsari; Aryo, Rakhmundia (Universitas Ahmad Dahlan, 2026)
Women-owned Micro, Small, and Medium Enterprises (MSMEs) in Indonesia play a crucial role in economic development. Yet, they still face challenges such as limited market access, capital, and digital literacy. Despite high female participation, their contribution to GDP remains stagnant, highlighting the need for more effective empowerment strategies. This study aims to examine the role of digitalization—including e-commerce, social media, digital bookkeeping, and digital payment methods—on the business turnover of women entrepreneurs in Klewer Market, Surakarta. This study contributes to the literature on women's entrepreneurship by providing empirical evidence from a traditional market context, highlighting both the opportunities and limitations of digital adoption. Quantitative methods were employed, utilizing survey data from 150 women-owned MSMEs selected through purposive sampling. Multiple linear regression using Ordinary Least Squares (OLS) was applied to assess the effect of digitalization on turnover. The results indicate that three aspects of digitalization—e-commerce, social media, and digital payments—have a positive and significant effect on business turnover, while digital bookkeeping has no significant impact due to low adoption. Most entrepreneurs still operate with low turnover, and only a few achieve higher revenues, indicating an unequal distribution of the benefits of digitalization. E-commerce expands market reach, social media strengthens customer relationships, and digital payments improve efficiency and accountability. However, gaps in digital and financial literacy continue to have broader impacts. In conclusion, digitalization is a strategic tool for improving women's business performance, but its success requires stronger digital literacy and technical support to ensure inclusive benefits in traditional markets.